PENGARUH PEMBELAJARAN KEWIRAUSAHAAN TERHADAP KESIAPAN BERWIRAUSAHA SISWA KELAS XII PASTRY SEKOLAH MENENGAH KEJURUAN NEGERI 9 BANDUNG - Pratomo, Raden Putra Kurnia; Mulyadi, Hari; Utama, Dian Herdiana (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Objectives - The purpose of this study is to see description of entrepreneurship learning and readiness of student entrepreneurship as well as the influence of entrepreneurial learning on entrepreneurial readiness. Design / methodology / approach - The design of this study is cross sectional method. This research uses descriptive approach with explanatory survey method. A total of 82 respondents were selected using probability sampling in the form of simple random sampling. A questionnaire was used as a research instrument to collect data from respondents. The analysis technique used is descriptive technique by using frequency distribution and verification technique by using simple linear regression analysis.Findings - Based on the results of research using descriptive analysis, the results obtained that entrepreneurial learning is in high category, and entrepreneurial readiness is in high category. While the verifikatif analysis, obtained the result that the influence of entrepreneurship learning on entrepreneurial readiness is in the category of being.Originality / value - This research provides a basis for understanding issues of entrepreneurship learning, and entrepreneurship readiness. The difference of this research with the previous research is located on the object that is the tourism vocational school that is Vocational School Negeri 9 Bandung, with the variables studied are entrepreneurial learning and entrepreneurial readiness, and using theory or reference that is different from previous researchers.